Burden of tuberculosis and TB/HIV co-infection in Dushanbe - B. P. Pirmakhmadzoda; Z. Kh. Tilloeva; Kh. S. Sharifzoda; O. Ya. Kabirov; K. A. Imomnazarova; S. M. Odinaeva (Туберкулез и болезни лёгких, 2021)
The objective of the study: to determine the burden of tuberculosis with concurrent HIV infection in Dushanbe and the prevalence of multiple drug resistant tuberculosis, to assess the treatment efficacy of drug susceptible and drug resistant tuberculosis depending on the HIV status of patients.Subjects: A cohort retrospective study was carried out assessing results of examination and treatment of all patients (1,838 people) registered for tuberculosis treatment from 01.06.2016 to 25.12.2019 in Dushanbe.Results. Among new tuberculosis cases, MDR is more often registered in HIV positive patients versus HIV negative patients (OR 2.3, 95% CI 1.1-4.9, p = 0.03). The chances of successful treatment of tuberculosis in HIV negative patients were higher versus HIV positive patients as well as in drug susceptible tuberculosis (OR 4.7, 95% CI 3.1-7.4; p < 0.000) versus drug resistant tuberculosis (OR 2.5, 95% CI 1.1-75.7; p = 0.03). The chances of tuberculosis cure did not differ statistically significantly among patients with different HIV status for both drug resistant and drug susceptible tuberculosis.